2009
DOI: 10.1016/j.bbabio.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and regulation of the violaxanthin cycle: The role of antenna proteins and membrane lipids

Abstract: The violaxanthin cycle describes the reversible conversion of violaxanthin to zeaxanthin via the intermediate antheraxanthin. This light-dependent xanthophyll conversion is essential for the adaptation of plants and algae to different light conditions and allows a reversible switch of photosynthetic light-harvesting complexes between a light-harvesting state under low light and a dissipative state under high light. The photoprotective functions of zeaxanthin have been intensively studied during the last decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
284
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(298 citation statements)
references
References 155 publications
8
284
1
5
Order By: Relevance
“…However, these photosynthetic parameters can be also affected by other mechanisms. In particular, different components of NPQ can be affected by the pH-dependent protonation of PsbS proteins [37,111], state transition [37,113,114], and photoinhibition [115]. The contribution of these processes to the total NPQ depends on environmental conditions [115,116] and the time of their development [117].…”
Section: Conditions Of Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these photosynthetic parameters can be also affected by other mechanisms. In particular, different components of NPQ can be affected by the pH-dependent protonation of PsbS proteins [37,111], state transition [37,113,114], and photoinhibition [115]. The contribution of these processes to the total NPQ depends on environmental conditions [115,116] and the time of their development [117].…”
Section: Conditions Of Measurementmentioning
confidence: 99%
“…The effect may be due to the complex mechanisms of photosynthetic stress in plants. It is known that changes in PRI are mainly connected with redox processes in the xanthophyll cycle [26,36], which is regulated by pH in the lumen of chloroplasts [111]. Transitions in the xanthophyll cycle can influence the nonphotochemical quenching and the quantum yield of photosystem II [111,112].…”
Section: Conditions Of Measurementmentioning
confidence: 99%
“…The main short-time response in many higher plants and microalgae when transferred from low to high light intensity is the synthesis of zeaxanthin from violaxanthin through the xanthopyll cycle [33,34]. In Chlamydomonas this response to high light shifts is well documented [4].…”
Section: Screening Of Insertional Mutants With An Altered Response Tomentioning
confidence: 95%
“…The synthesis of zeaxanthin in Chlamydomonas cells after exposure to a high light stress [35] and other kind of stress conditions [36] has been previously reported. It has been demonstrated that this zeaxanthin is produced from violaxanthin via the xanthophyll cycle [33], but neither the enzyme nor the gene encoding this putative violaxanthin de-epoxidase (VDE) has been identified yet in Chlamydomonas. In the sequenced genome of this chlorophyte no orthologues to plant or other algal VDE genes have been identified [37].…”
Section: Screening Of Insertional Mutants With An Altered Response Tomentioning
confidence: 99%
“…Essa diferença é a razão da incerteza quanto à presença funcional de um ciclo das xantofilas típico em algas vermelhas, ou da função destes pigmentos na dissipação térmica imediata, por exemplo. Por outro lado, trabalhos realizados em plantas terrestres têm indicado que a zeaxantina também pode ser encontrada livre nos tilacoides (Havaux et al, 2007;Jahns et al, 2009;, da mesma forma que nas membranas plasmáticas de cianobactérias que acumulam zeaxantina quando mantidas em alta intensidade de luz (Masamoto et al, 1999). Dessa forma, seria plausível propor que há duas localizações possíveis para zeaxantina, enquanto nas antenas haveria redução, fora das antenas poderia haver um aumento na concentração, assim a competição entre essas duas localizações poderia explicar o comportamento de aumento nos dias iniciais e redução nos dias finais.…”
Section: Discussionunclassified